Medan City Economic Transformation: The Role of Management in Development of the Creative Industry Sector - Supriadi, Supriadi; Helmi, Tengku Ahmad; Tarigan, Nur M. Ridha; Bangun, Mira Srinina (Medan Resource Center, 2024)
This research examines the economic transformation of Medan City through the development of the creative industry sector, with a focus on the role of government management in supporting the growth of the sector. This study uses a qualitative method with a case study approach, involving in-depth interviews with stakeholders, document analysis, and field observations. The results of the study show that the creative industry in Medan has developed rapidly and made a significant contribution to the city's Gross Regional Domestic Product (GDP). The role of government management, especially through incentive policies, infrastructure development, and educational programs, has proven important in creating an ecosystem that supports innovation and collaboration. However, challenges such as limited access to funding and lack of qualified human resources are still obstacles to further development. The research also highlights the positive social and economic impacts of the sector, including job creation and the preservation of local culture. In conclusion, the development of creative industries in Medan City shows great potential to become a major pillar in the city's economic transformation, with important implications for development policies in other regions.